Determination of the dynamic complex modulus of viscoelastic materials using a time domain approach. (December 2015) - Bonfiglio, Paolo; Pompoli, Francesco
Abstract: Viscoelastic and poroelastic materials are widely used in multilayer panels for noise control. They are usually used as an inner decoupling layer in double wall systems in order to increase the sound transmission loss of a bare plate. In order to correctly simulate the acoustical behaviour of such systems, it is necessary to measure the elastic parameters of these materials (storage and loss moduli, and Poisson's ratio). Physical properties related to pore morphology also need to be determined for open cell structures. Most of the materials used in trimmed panels can show elastic parameters that vary with frequency, thus a quasi-static measurement technique is not accurate enough to consider such viscoelasticity effects. This paper focuses on the estimation of complex modulus as a function of the frequency of isotropic viscoelastic materials. In particular, the tested material is positioned between two plates, with one of them being excited by an electromagnetic shaker. Using a sine burst as an excitation signal, the accelerometric response in the time domain is measured at the top and bottom plates. The time of flight between the plates and the envelope function of time domain acceleration at the top plate are then found. A transfer matrix model of the experimental setup is used to inversely estimate the complex modulus of the materials once the remaining mechanical and physical properties have been fixed. The results will be presented and discussed for different materials and compared with well-established quasi-static and dynamic techniques.